Macrocycle‐Based Crystalline Sponge that Stabilizes and Lights Up Cationic Aggregation‐Caused Quenching Dyes - Sun, Xin; Yang, Yu‐Dong; Chen, Xu‐Lang; Sun, Ai‐Huan; Xiang, Jun‐Feng; Gong, Han‐Yuan (Advanced optical materials, 2021)
Solid‐state fluorescent materials play a critical role in the manufacture of light‐emitting diodes, laser dyes, storage materials, and fluorescence sensors. However, it remains challenging to produce solid‐state fluorescent materials using traditional organic dyes since most are subject to aggregation‐caused quenching (ACQ) in the solid state. Here, a macrocycle‐derived crystalline framework is reported that captures various cationic test‐ACQ dyes (e.g., Basic Red 2 (BR2)) and stabilizes them in a fluorescent form. Cyclo[3](1,3‐benzene)[3](4,6‐benzene)(1,3‐dicarboxylic acid), CA‐3, is used as the core macrocyclic building block. When allowed to coordinate with Zn(NO3)2•6H2O or Cd(NO3)2•4H2O, crystalline sponge (CS‐Zn or CS‐Cd) is obtained. In the case of CS‐Zn, nano‐sized cavities are observed in the solid state that serve as containers to capture the cationic ACQ dye BR2 with loading yields up to 14.6 wt% and emission enhancements up to 41× of those seen for solid BR2. The resulting dye‐containing material, CS‐Zn@BR2, displays high stability in water or selected organic solvents at room temperature or under reflux, or when heated at 300 °C for 1 h open to the air, or in the presence of sodium hypochlorite solution (3.0 mm). This study highlights a new strategy for rendering fluorescent ACQ dyes in the solid state. A macrocycle‐based crystalline sponge selectively captures cationic aggregation‐caused quenching dyes with high loading quantity, and further, enormously improves the dye emission properties in solid state. Moreover, crystalline sponge container can enhance the structure and optical stability of tested dye‐containing solid state fluorescence materials under treatment of solvents at room or reflux temperatures, or at 300 °C in air or oxidant (NaClO) damage.